2015
DOI: 10.1080/19336896.2015.1027855
|View full text |Cite
|
Sign up to set email alerts
|

Targeting prion protein interactions in cancer

Abstract: In recent years, prion protein (PrP(C)) has been considered as a promising target molecule for cancer therapies, due its direct or indirect participation in tumor growth, metastasis, and resistance to cell death induced by chemotherapy. PrP(C) functions as a scaffold protein, forming multiprotein complexes on the plasma membrane, which elicits distinct signaling pathways involved in diverse biological phenomena and could be modulated depending on the cell type, complex composition, and organization. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 40 publications
0
39
0
4
Order By: Relevance
“…30 The miR-200 family is a cluster of miRNAs closely linked to the epithelial–mesenchymal transition (EMT) and is believed to have an essential role in tumour suppression by inhibiting EMT, the initiating step of metastasis. 31 A number of experimental studies show that changes in miR-200 family levels have been associated with enhanced tumorigenesis and are significantly correlated with decreased survival caused by lung cancer and other cancers. 32 Many studies have reported that PrP C can stimulate the outgrowth of neurites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The miR-200 family is a cluster of miRNAs closely linked to the epithelial–mesenchymal transition (EMT) and is believed to have an essential role in tumour suppression by inhibiting EMT, the initiating step of metastasis. 31 A number of experimental studies show that changes in miR-200 family levels have been associated with enhanced tumorigenesis and are significantly correlated with decreased survival caused by lung cancer and other cancers. 32 Many studies have reported that PrP C can stimulate the outgrowth of neurites.…”
Section: Discussionmentioning
confidence: 99%
“…All of these functions imply that PrP may be involved in tumorigenesis. 31 The role of the miR-200 family in TSEs is not very clear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, more recent studies suggested that PrP C plays a role in pluripotency and differentiation of embryonic stem cells [22], cell proliferation and differentiation [2328], and muscle cell regeneration [29], through the direct activation of the Src-family kinase Fyn, at least as far as the CNS effects [30]. Starting from these observations PrP C has been intriguingly involved in the development of human tumors [22, 31], including glioblastoma [32, 33], and gastric [34], breast [35], prostate [36], and colorectal [37] carcinomas. For example, PrP C expression was correlated with increased cell proliferation in gastric cancer cell lines [18, 38], and PrP C overexpression was shown to provide cancer cells with resistance to cytotoxic agents [36], and higher invasive properties [39].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent extra views report, Santos and colleagues pointed out, as good candidate for therapeutic interventions, the PrP c role as a scaffold protein organizing membrane platforms and the search for specific partners within tumor cells, extracellular matrix, and soluble factors secreted from tumor cells. 12 Based on our recent FIGURE 2. Calcium-dependent dissassembly of cell-cell junctions is sufficient to address PrP c to the nucleus and to delocalize Src from cell-cell contacts.…”
Section: Prp C Interaction With Junctional and Nuclear Partners: A Romentioning
confidence: 99%
“…9 We will discuss how these observations in tumoral and non-tumoral intestinal epithelial cells can shed a new light on recent data that identified PrP c as a potential important player in tumor biology in a large range of tissues. 11,12 6 and components of desmosomes: desmoglein 2, g-catenin (also known as plakoglobin), plakophilin 2A and desmoplakin (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%